LYON-UNIVERSITY HOSPITAL EXPERIENCE WITH GEMTUZUMAB OZOGAMICIN THERAPY IN ACUTE MYELOID LEUKEMIA: A ‘REAL-LIFE’ STUDY - Xavier Thomas; Marica Laurino; sandrine loron; marie-virginie larcher; gaëlle fossard; mohamed elhamri; alexandre deloire; marie balsat; fiorenza barraco; hélène labussière; sophie ducastelle; myriam renault; et al. (Mediterranean Journal of Hematology and Infectious Diseases)
One-hundred and four adults with newly diagnosed or relapsed/refractory acute myeloid leukemia (AML) were treated with fractionated doses of gemtuzumab ozogamicin (GO) at one-single French center over a 10-year period. We attempted to define predictive factors for response and survival. The overall response rate was 70% (86% in newly diagnosed and 67% in relapsed/refractory AML). Disease-free survival (DFS) and overall survival at 3 years after GO treatment was 31% and 29%, respectively. Mortality during induction was 7%. Among remitters, allogeneic hematopoietic stem cell transplantation can be performed in 33 cases (45%). DFS at 3 years was 54%. Incidences of transplant-related mortality, grade ≥ 3 acute graft-versus-host (GvH) disease, and extensive chronic GvH disease were 15%, 12%, and 27%, respectively.No sinusoidal obstruction syndromes were reported among allografted patients as among the other patients in the studied cohort. GO-based chemotherapy is a viable option for treatment of newly diagnosed and relapsed/refractory AML patients, and is a feasible schedule as a bridge to allogeneic transplant.